Environmental Pollution to Blame for Depressive Disorder? - Segovia-Mendoza, Mariana; Palacios-Arreola, Margarita Isabel; Pavón, Lenin; Becerril, Luis Enrique; Nava-Castro, Karen Elizabeth; Amador-Muñoz, Omar; Morales-Montor, Jorge (International journal of environmental research and public health, 2022)
Public concern has emerged about the effects of endocrine-disrupting compounds (EDCs) on neuropsychiatric disorders. Preclinical evidence suggests that exposure to EDCs is associated with the development of major depressive disorder (MDD) and could result in neural degeneration. The interaction of EDCs with hormonal receptors is the best-described mechanism of their biological activity. However, the dysregulation of the hypothalamic-pituitary-gonadal adrenal axis has been reported and linked to neurological disorders. At a worldwide level and in Mexico, the incidence of MDD has recently been increasing. Of note, in Mexico, there are no clinical associations on blood levels of EDCs and the incidence of the MDD. Methodology: Thus, we quantified for the first time the serum levels of parent compounds of two bisphenols and four phthalates in patients with MDD. The levels of di-ethyl-hexyl-phthalate (DEHP), butyl-benzyl-phthalate (BBP), di-n-butyl phthalate (DBP), and di-ethyl-phthalate (DEP), bisphenol A (BPA), and bisphenol S (BPS) in men and women with or without MDD were determined with a gas chromatograph-mass spectrometer. Results/conclusion: We found significant differences between concentrations of BBP between controls and patients with MDD. Interestingly, the serum levels of this compound have a dysmorphic behavior, being much higher in women (~500 ng/mL) than in men (≤10 ng/mL). We did not observe significant changes in the serum concentrations of the other phthalates or bisphenols tested, neither when comparing healthy and sick subjects nor when they were compared by gender. The results point out that BBP has a critical impact on the etiology of MDD disorder in Mexican patients, specifically in women.